2021
DOI: 10.3390/polym13040516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polyacrylonitrile Nonwoven Mats and Silver–Gold Bimetallic Nanoparticle-Decorated Nonwoven Mats for Potential Promotion of Wound Healing In Vitro and In Vivo and Bone Growth In Vitro

Abstract: We prepared polyacrylonitrile (PAN) and urchin-like Ag–Au bimetallic or Ag nanoparticle-decorated PAN nonwoven mats using electrospinning and evaluated them in vitro and in vivo for wound healing, antibacterial effects on skin tissue, and promotion of bone ingrowth in vitro. A facile, green, low-temperature protocol was developed to obtain these nonwoven mats. The sterilization rate of urchin-like Ag–Au bimetallic and Ag nanoparticle-decorated PAN nonwoven mats against Staphylococcus aureus was 96.81 ± 2.81% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Collagen wound dressings contain collagen blended with natural and synthetic polymers such as polyethylene oxide, poly (L-lactic acid), hyaluronic acid, elastin and silk fibroin, alginate, chitosan, etc [ 73 , 81 , 82 , 83 , 84 , 85 ]. These blended fabrications have incorporated other additives such as insulin [ 86 ], antibiotics [ 87 , 88 , 89 , 90 , 91 , 92 ] or gold nanoparticles [ 93 , 94 , 95 ] and have been tested mostly in in vitro studies or small animal models of wound healing. An evidence-based review of clinical studies on antibacterial integrated collagen wound dressings indicated that most studies were limited by small sample sizes and mixed chronic wound etiologies [ 46 ].…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen wound dressings contain collagen blended with natural and synthetic polymers such as polyethylene oxide, poly (L-lactic acid), hyaluronic acid, elastin and silk fibroin, alginate, chitosan, etc [ 73 , 81 , 82 , 83 , 84 , 85 ]. These blended fabrications have incorporated other additives such as insulin [ 86 ], antibiotics [ 87 , 88 , 89 , 90 , 91 , 92 ] or gold nanoparticles [ 93 , 94 , 95 ] and have been tested mostly in in vitro studies or small animal models of wound healing. An evidence-based review of clinical studies on antibacterial integrated collagen wound dressings indicated that most studies were limited by small sample sizes and mixed chronic wound etiologies [ 46 ].…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…Collagen is also used as a surface coating to enhance moisture retention and promote cell adhesion within scaffolds/matrices [ 73 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Water retention is important to keep the wound bed moist.…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…In tissue engineering studies, nonwovens have been investigated as scaffolds that are directly transplanted into the injured site [ 1 , 22 , 25 , 28 , 33 ]. However, to the best of our knowledge, nonwovens have never been used for explant culture of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the effects of fiber materials [ 4 ] and orientation patterns on cell attachment and growth [ 7 , 26 , 30 ]. Several studies have focused on the surface modification of nonwoven materials to enhance biological responses, such as antibacterial [ 1 , 17 ] and bone regeneration [ 22 , 25 ]. As cells can be expanded three-dimensionally, the woven pores and thickness may be important.…”
Section: Discussionmentioning
confidence: 99%
“…As for attenuated total reflection (ATR) infrared (IR) absorption spectroscopy, it measures both interface and bulk regions due to the long evanescent field’s decay length (several hundred nm) [ 11 , 12 ]. Therefore, a method is required to analyze structures of vicinal water, whose property is different from bulk [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%